U/Th, age model and stable isotope data from the Last Glacial Maximum to the Early Holocene in Sibaki Cave, Southwestern Iran - Soleimani, Mojgan; Nadimi, Alireza; Koltai, Gabriella; Dublyansky, Yuri; Carolin, Stacy A; Spötl, Christoph (PANGAEA, 2023)
Paleoclimate records from the Middle East are sparse in comparison to other regions. The records as such could be useful to improve our understanding of natural variability in atmospheric circulation patterns. In particular, there are no paleoclimate studies in Iran that span the transition from the Last Glacial Maximum (LGM) to the Holocene based on speleothems. In light of the significant changes in the global climate since the last glacial period (LGM to Early Holocene), it is useful to examine regional climate variability during this time period to gain a better understanding of the climate sensitivity of different areas. In this study we report the first stalagmite records spanning the LGM and the corresponding deglacial transition in southwestern Iran. The sample was collected from Sibaki cave (29֯ 48' 54" N, 51֯ 35' 47" E) in southwestern Zagros, Iran. The cave entrance opens at 1275 m a.s.l. on a NE-facing slope of 1275 m a.s.l. There were no active drips onto SIB-4 when the stalagmite was collected in February 2019.
Keywords: d13C; d18O; Iran; stalagmite; U-Th dating